PENGARUH MOTIVASI KERJA, MANAJEMEN WAKTU, DAN STRES KERJA TERHADAP KINERJA PERKERJA PARUH WAKTU YANG BERSTATUS MAHASISWA DI MAGELANG - Prasetya, Miftachul Huda Adi; Alkadri Kusalendra Siharis (Transpublika Publisher, 2023)
This study aims to look at the effect of work motivation, time management, and work stress on the performance of part-time student workers in Magelang and provide references related to improving part-time student performance for part-time students and business owners. This study uses a quantitative methodology. 60 people were studied using a purposive sampling technique. Multiple regression analysis was performed for data analysis. The test results show that work motivation has a sizable positive impact on the performance of part-time students. Part-time student workers will be motivated to work effectively, thereby increasing their performance, if they have goals to achieve and a sense of purpose.